Open Access Series of Imaging Studies (OASIS): Longitudinal MRI Data in Nondemented and Demented Older Adults - Marcus, Daniel S. (2010)
The Open Access Series of Imaging Studies (OASIS) is a series of neuroimaging data sets that is publicly available for study and analysis. The present MRI data set consists of a longitudinal collection of 150 subjects aged 60 to 96 all acquired on the same scanner using identical sequences. Each subject was scanned on two or more visits, separated by at least one year for a total of 373 imaging sessions. Subjects were characterized using the Clinical Dementia Rating (CDR) as either nondemented or with very mild to mild Alzheimer‘s disease (AD). 72 of the subjects were characterized as nondemented throughout the study. 64 of the included subjects were characterized as demented at the time of their initial visits and remained so for subsequent scans, including 51 individuals with CDR 0.5 similar level of impairment to individuals elsewhere considered to have ‘mild cognitive impairment’. Another 14 subjects were characterized as nondemented at the time of their initial visit (CDR 0) and were subsequently characterized as demented at a later visit (CDR > 0). The subjects were all right-handed and include both men (n=62) and women (n=88). For each scanning session, 3 or 4 individual T1-weighted MRI scans were obtained. Multiple within-session acquisitions provide extremely high contrast-to-noise making the data amenable to a wide range of analytic approaches including automated computational analysis. Automated calculation of whole brain volume is presented to demonstrate use of the data for measuring differences associated with normal aging and AD.